CURRENT ISSUES OF QUALIFICATION AND DIFFERENCE BETWEEN THE ACT OF TERRORISM AND SABOTAGE - Vicen, Vlastimil (SUPREMAȚIA DREPTULUI, 2017)
The article is dedicated to the research of peculiarities of qualification of the act of terrorism and sabotage. The following criminal legal description of these crimes is aimed at determining their common and individual characteristics that allows to differentiate their law enforcement activities. The study focuses on the issue of the need to improve anti-terrorist legislation, which is directly aimed at combating and preventing terrorism. For this purpose, the proposed definition of the content of some concepts is an important step to clarify the content and extent of the relevant criminal law standards and separate them from related illegal actions.